A Way of Determining Accessory Pathway based on 12 Lead Electrocardiogram - Lucianan Selly Yudhatama; Ignatius Yansen; Endin Nokik (UHAMKA Press, 2019)
ABSTRACT Atrioventricular Reentrant Tachycardia (AVRT) is an ECG disorder caused by the presence of an accessory pathway. Characterized by short PR intervals and delta waves in asymptomatic patients. The scientific papers aims is how to determine the location of the accessory pathway in manifest AVRT patients based on a 12 Lead ECG. The method used in scientific papers is descriptive by looking at the similarities or gaps between the theories on the application of cases. The results of this study case obtained 4 patients with a diagnosed manifest AVRT and to determine the location of the accessory pathway on a 12 lead ECG the author referred to the Arruda algorithm. The conclusion of this study case is to determine the location of the accessory pathway with a 12 lead ECG in the initial investigation which is very appropriate for efficiency for the ablation procedure because it does not require a long time in determining the accessory pathway location with the EP study. Keyword : Atrioventricular Reentry Takikardia, Accessory Pathway, Electrocardiogram Cara Menentukan Lokasi Jaras Tambahan Berdasarkan 12 Lead Electrokardiogram ABSTRAK Atrioventricular Reentrant Tachycardia (AVRT) adalah kelainan EKG yang disebabkan oleh adanya jaras tambahan. Ditandai dengan interval PR yang pendek dan gelombang delta pada pasien asimtomatik. Penulisan karya tulis ilmiah ini bertujuan untuk mengetahui cara menentukan lokasi jaras tambahan pada pasien AVRT yang manifest berdasarkan EKG 12 Lead. Metode yang digunakan dalam penulisan karya tulis ilmiah ini adalah deskriptif dengan melihat kesamaan atau kesenjangan antara teori pada penerapan kasus. Hasil dari studi kasus ini didapatkan 4 pasien dengan diagnosa AVRT yang manifest dan untuk menentukan lokasi jaras tambahan pada EKG 12 lead penulis mengacu pada Algoritma Arruda. Kesimpulan dari studi kasus ini adalah menentukan lokasi jaras tambahan dengan EKG 12 lead pada pemeriksaan penunjang awal sangat tepat untuk efisiensi pada tindakan ablasi karna tidak memerlukan waktu lama dalam menentukan lokasi jaras tambahan dengan EP study. Kata Kunci : Atrioventricular Reentry Takikardia, Jaras Tambahan, Elektrokardiogram